(untitled) (Journal of the College of Languages (JCL), 2019)
Field of translation is sampled with many types of translation, such as the literary, scientific, medical, etc. The translation of grammatical aspects has always been with difficulties. Political translation is the focus here. There are many general problems faced by translators when translating political texts from Arabic into Spanish. The aim here is to clarify the definition of functions or terms within the text, and to arrive at the correct from of translation of such texts from Spanish into Arabic. It is worth mentioning that the paper is of two parts: the first exemplifies what is meant by translation, the prerequisites of a translator, along with mentioning the methods followed in translating political texts. The second takes care of tackling political terms in Spanish, and how they are translated into Arabic with the help of examples. Finally, a glossary is made of some common poitical terms in newspapers and mass media and how they are translated into Arabic. Resumen Este trabajo de investigación da una clara definición de los textos políticos y explicar la forma correcta de la traducción de los textos políticos del español al árabe. Indica al concepto general sobre la traducción, los requisitos y factores de los traductores principales, además de las técnicas de la traducción . Se clara también las expresiones y giros políticos en lengua española y un ejemplo de una noticia política en español y su traducción al árabe, además de un anexo contiene algunos términos políticos español-árabe.